Pengaruh Trend Fashion, Halal Lifestyle, dan Celebrity Endorser Terhadap Minat Beli Hijab Generasi Z di DKI Jakarta - Sholikha, Amaliyah; Rahmi, Mira (LPPM Universitas Bina Sarana Informatika, 2024)
The rapid growth of the Muslim population in Indonesia has created an increase in the demand for halal fashion products, especially hijabs. This demand is driven by the significant role of the Z generation, who desire to express their creativity through embroidery. This generation has become a major factor in the rapid growth of Indonesia’s hijab fashion world. The aim of this study is to identify the influence of fashion trends, halal lifestyles, and well-known endorsers on the interest in buying hijabs among the Z generation at DKI Jakarta. The study uses a quantitative approach involving respondents from the Z generation who have an interest in and experience shopping for hijabs. The sample consisted of 120 Z-generation Muslim women, who were well-known endorsers and lived in DKI Jakarta. The samples were selected using non-probability sampling techniques with purposive sampling. Data collection was carried out by distributing questionnaires with multiple linear regression data analysis techniques using partial least squares (PLS). The findings show that fashion trend variables, halal lifestyle, and well-known endorsers influence interest in purchasing the Z-generation hijab. This research is expected to contribute to the hijab industry, remain relevant to fashion trends, develop halal lifestyles, and pay attention to the use of authentic renowned endorses in hijabs.